(untitled) (Academicia Globe: Inderscience Research, 2021)
These sports organizations and associations are organized by schoolchildren, students, workers, the military, law enforcement officers and other representatives of various fields. The main goals and objectives of these organizations are to engage the public in physical culture and sports, to hold various competitions, to prepare and participate in international sports competitions by organizing various teams. Also, public health sports events, various sports holidays and competitions, the use of national action games in visual sports systems. Public outreach is one of the most important activities of any sports organization or association.